Distribution of Pb and Zn and their Chemical Specieisations in the Paddy soils from the Kočani field (Macedonia) (Geologica Macedonica, 2013)
The distribution and chemical specifications of Pb and Zn in the paddy soils of Kočani Field, Macedonia, were investigated using a sequential extraction procedure. This study was carried out in order to develop an understanding of the metal contamination found in the area which is due to historical and recent mining operations around Kočani Field. The paddy soil sample from location VII–2 in the vicinity of Zletovo mine in the western part of Kočani Field was found to contain highly elevated concentrations of Pb and Zn which are under reduction conditions very unstable and mobile. According to the total Pb and Zn concentrations, their mobility characteristics and the index of geoaccumulation for all studied soil samples, it is observable that the paddy soil sample from location VII–2 represents a potential environmental risk.